2022
DOI: 10.3390/rs14061379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crop Type Based on C-AENN Using Time Series Sentinel-1A SAR Data

Abstract: Crop type identification is the initial stage and an important part of the agricultural monitoring system. It is well known that synthetic aperture radar (SAR) Sentinel-1A imagery provides a reliable data source for crop type identification. However, a single-temporal SAR image does not contain enough features, and the unique physical characteristics of radar images are relatively lacking, which limits its potential in crop mapping. In addition, current methods may not be applicable for time -series SAR data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The variation of the NDMI index in relation to time (t, days) was described by equation (10) under conditions of R 2 =0.934, p<0.001, F=47.18. The variation of the NDVI index in relation to time (t, days) was described by equation (11) under conditions of R 2 =0.941, p<0.001, F=53.92. The variation of the NBR index in relation to time (t, days) during the study period was described by equation (12), under conditions of R 2 =0.961, p<0.001, F=83.225.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of the NDMI index in relation to time (t, days) was described by equation (10) under conditions of R 2 =0.934, p<0.001, F=47.18. The variation of the NDVI index in relation to time (t, days) was described by equation (11) under conditions of R 2 =0.941, p<0.001, F=53.92. The variation of the NBR index in relation to time (t, days) during the study period was described by equation (12), under conditions of R 2 =0.961, p<0.001, F=83.225.…”
Section: Resultsmentioning
confidence: 99%
“…In general, high levels of statistical accuracy were communicated in estimating production based on remote sensing techniques, due to the fact that the vegetation reflects well through the status of the plants, the chlorophyll content, or other representative physiological indices, the vegetation conditions, the technological level of the process of production, and these aspects are well and correctly captured in the satellite images, as data in the form of spectral information (Guo et al, 2022). For example, Amankulova et al ( 2023) have reported very high accuracy (RMSE with values between 121.9 and 284.5 kg ha -1 ) in the prediction of sunflower production, based on satellite images in the Sentinel-2 system.…”
Section: Resultsmentioning
confidence: 99%
“…31 Additionally, in the field of image classification, convolutional neural networks (CNNs) have gained widespread acceptance due to their proficiency in effectively extracting spatial-temporal features. 32 For instance, Guo et al 33 introduced a convolutional-autoencoder neural network (C-AENN), which combined 1D-CNN and SAE techniques. When compared to traditional machine learning methods, the results demonstrated that C-AENN outperformed them in the task of crop classification, even with limited training data.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have worked on IDSs in which machine learning (ML) and deep learning (DL) models play a key role [ 10 ]. ML and DL techniques are widely used in different fields, such as in agriculture [ 11 ], medical [ 12 ], and automobile industries [ 13 , 14 ]. DL is a branch of ML, and it is generalizable to new problems with complicated and high-dimensional data.…”
Section: Introductionmentioning
confidence: 99%